European Standards of Judicial Control at the Pre-Trial Stage of Criminal Proceedings - Kuntso, Sergii (Global Prosperity, 2026)
This article examines European standards of judicial control at the pre-trial stage of criminal proceedings and their implementation in national criminal procedure of Ukraine. The relevance of the study is determined by need to harmonize Ukrainian criminal procedural legislation with standards of the Council of Europe and case law of the European Court of Human Rights. The purpose of this research is to identify key models and principles of judicial control in pre-trial proceedings and to assess their integration into Ukrainian legal practice. The methodological basis of the study includes comparative legal analysis, systemic-structural and formal-legal methods, which allow examination of international standards and national legislation in their interrelation. It is established that judicial control at the pre-trial stage is a fundamental guarantee of protection of human rights in relation to the legality of detention, searches, seizures, and other procedural coercive measures. The study highlights that European standards emphasize the independence and impartiality of the investigating judge, requirement for effective judicial review, and the principle of proportionality in restricting fundamental rights. The analysis of the case law of the European Court of Human Rights demonstrates persistent challenges in ensuring effective judicial oversight in Ukraine regarding the duration of detention and the quality of judicial reasoning. Findings indicate Ukraine has advanced in aligning its criminal procedure with European standards, but further improvement is required to ensure compliance with Articles 5 and 6 of the European Convention on Human Rights. Findings may contribute to improvement of national legislation and judicial practice.